Mindfulness-Based Cognitive Therapy in Major depressive disorder - systematic review and metanalysis - Rafaela Liberali
Abstract Introduction: MBCT practices increases the ability of concentration and attention, as well is particularly effective for people with current and treatment-resistant depression. Objective: To analyze the effects of the application of MBCT in symptoms of MDD. Methods: systematic review and meta-analysis. To find suitable studies, we searched PubMed/MEDLINE's database using the keywords mindfulness and major depressive disorder. Studies in English published between 2003 and 2015 were selected. The studies were evaluated according to their methodological quality by PEDro scale (score greater than 3), studies that showed empirical evidence, had an experimental study design (randomized and non-randomized), and whose full text was available. For the meta-analysis, we used a random-effects model with standardized mean differences and 95% confidence intervals. Results: Fourteen es were included, of which three were non-randomized, with only one group with intervention of MBCT, and 11 were randomized studies, divided into two-group samples and three-group samples. The non-randomized studies showed a PEDro score of 5, while the two-group and three-group randomized studies showed PEDro scores of 5-10 and 6-9, respectively. In the meta-analysis, the four randomized studies selected revealed a moderate effect of MBCT on the outcome of depression symptoms, with a mean difference of -0.52 (95% CI: -1.050 to -0.002; p = 0.04). Conclusion: The MBCT presented as a promising alternative for the treatment of this disorder.